Historical dictionary of the Baptists - Brackney, William H. (Historical dictionaries of religions, philosophies, and movements, 2009)
"The term Baptist originated with the Anabaptists, who are historically linked to the English Separatist movement of the 16th century. Today, the largest national community of Baptists worldwide is in the United States, with 38.8 million members. The Southern Baptist Convention is the largest Protestant denomination in the United States. Although Baptist churches are located throughout the country, the majority of Baptists live in the southern United States, and the Baptist faith has historically exerted a powerful influence in that region - with 110 million members worldwide." "This second edition of the Historical Dictionary of the Baptists expands upon the first edition with an updated chronology, an introductory essay, a bibliography, and hundreds of cross-referenced dictionary entries on important events, doctrines, church founders, leaders, and other prominent figures. This volume commemorates the 400th anniversary of the founding of the Baptist movement in 1609."--BOOK JACKET.